Determinação de resíduos de agrotóxicos em café verde empregando QuEChERS e UHPLC-MS/MS - Alves, Larissa da Silva (2020)
Coffee is one of the most consumed beverages in the world and due to climatic diversity, reliefs, altitudes and latitudes Brazil is able to produce good quality coffee beans. Brazil is currently the largest producer and exporter of coffee and the second largest consumer. During the production process, different types of pesticides are used in several stages to prevent or eliminate pests that may impair productivity. However, due to the side effects caused by these pesticides, there should be a control of the amount of pesticide residues present in green coffee beans to ensure consumer health and export of coffee beans. In this work, a sample preparation method was developed evaluating QuEChERS method (citrate, acetate and original versions) for extraction of compounds and the d-SPE and LLE techniques for clean-up of the extract. The sorbents C18, PSA, GCB, Z-Sep+ and MgSO4 were evaluated using the d-SPE technique and the solvents dichloromethane and hexane in the LLE. The multiresidue method developed determined residues of 31 pesticides in green coffee beans, using high-performance liquid chromatography tandem mass spectrometry (UHPLC- MS/MS). Sample preparation was performed with 5 g of sample, addition of 5 mL of ultrapure water, extraction with 10 mL of acetonitrile, partition with salts (4 g of MgSO4 and 1 g NaCl) and clean-up with C18, PSA, GCB and MgSO4. The method was validated evaluating the parameters linearity, accuracy, precision, limit of detection (LOD), limit of quantification (LOQ) and matrix effect. The determination of pesticide residues on green coffee samples presented to be simple, fast and effective. The validation results, evaluated by recovery assays at 3 spiked levels, were satisfactory, with recoveries from 70 to 120%, RSD ≤ 20%, linearity from 0.5 to 20 μg L-¹, determination coefficient r²> 0.99, LOD from 0.003 to 0.015 mg kg-¹ and LOQ from 0.01 to 0.05 mg kg-¹. The proposed method was applied to green coffee bean samples produced in Brazil and carbofuran residues were found in 71% of the analyzed samples. The robustness and efficiency of the proposed method allows it to be applied in routine analyzes.